Adopting a Theophylline-Responsive Riboswitch for Flexible Regulation and Understanding of Glycogen Metabolism in Synechococcus elongatus PCC7942 - Chi, Xintong; Zhang, Shanshan; Sun, Huili; Duan, Yangkai; Qiao, Cuncun; Luan, Guodong; Lu, Xuefeng (Frontiers in Microbiology, 2019)
Cyanobacteria are supposed to be promising photosynthetic microbial platforms recycling carbon dioxide driven by solar energy into biomass and bioproducts. Glycogen synthesis serves as an essential natural carbon sink mechanism, storing a large portion of energy and organic carbon source from photosynthesis. Engineering glycogen metabolism to harness and rewire carbon flow is an important strategy to optimize efficacy of cyanobacteria platforms. ADP-glucose pyrophosphorylase (GlgC) catalyzes the rate-limiting step for glycogen synthesis. However knockout of glgC fails to promote cell growth or photosynthetic production in cyanobacteria, on the contrary the glgC deficiency impairs cellular fitness and robustness. In this work, we adopted a theophylline-responsive riboswitch to engineer and control glgC expression in Synechococcus elongatus PCC7942, and achieved flexible regulation of intracellular GlgC abundance and glycogen storage. With this approach, glycogen synthesis and glycogen contents in PCC7942 cells could be regulated in a range from about 40% to 300% of the wildtype levels. In addition, the results supported a positive role of glycogen metabolism in cyanobacteria cellular robustness. When glycogen storage was reduced, cellular physiology and growth under standard conditions was not impaired, while cellular tolerance toward environmental stresses was weakened. While when glycogen synthesis was enhanced, cells of PCC7942 displayed optimized cellular robustness. Our findings emphasized the significance of glycogen metabolism for cyanobacterial physiology and the importance of flexible approaches for engineering and understanding cellular physiology and metabolism.